Penerapan Metode SMARTER dalam Pendukung Keputusan Penerimaan Operator Komputer - Sri Novida Sari (JISTI: Jurnal Ilmu Komputer, Sistem Informasi dan Teknologi Informasi, 2025)
The vacancy of computer operator staff creates problems such as the delivery of information regarding school administration and activities, which cannot run smoothly. The problems experienced make the school conduct a computer operator recruitment selection to obtain results in accordance with the desired criteria. The computer operator recruitment selection process requires a series of predetermined assessments. The many assessment provisions from the selection process stages, then a decision support system is needed to help the selection process become more effective and efficient. The solution to the problems discussed in this study can be done by building a decision support system using the SMARTER method. The Simple Multi-Attribute Rating Technique Exploiting Ranks (SMARTER) method is a multi-criteria decision-making method that uses a weighting range between 0 and 1, thus simplifying the calculation and comparison of values ​​for each alternative. Based on previous research, it is said that this method can be used as a decision maker that is easy to learn, in addition to the calculations carried out in this method are very simple when compared to several other methods. The application of the SMARTER method in the decision support system for computer operator recruitment selection is expected to provide benefits in improving the quality and efficiency of the selection process. In addition, the results of this decision support system are expected to ensure that selected candidates have the qualifications that meet the needs. The application of the SMARTER method to the computer operator recruitment selection decided that alternative with code A4 was selected as a computer operator, with a final score of 1.666. Another alternative with code A3 was ranked second and alternative with code A10 was ranked third, both alternatives obtaining the same final score of 1.535.